The use of monte carlo simulation to predict vancomycin dosage for methicillin-resistant staphylococcus aureus in Thai patients of various ages and with varying degrees of renal function - Krairerk Pitaksontayothin (2018)
© 2017 Krairerk Pitaksontayothin, Wichai Santimaleeworagun, Manat Pongchaidecha, Jantana Houngsaitong, Panuwit Srisena This Work is licensed under Creative Common License Background: To our knowledge, no study reported so far has investigated appropriate vancomycin dosing, which is important for treatment of methicillin-resistant Staphylococcus aureus (MRSA) infection in Thai patients of various ages and with varying degrees of renal function. Objectives: To predict vancomycin dosing for MRSA in Thai patients of various ages and with varying degrees of renal functions. Methods: Monte Carlo simulation and minimal inhibitory concentration (MIC) distribution of MRSA from a hospital in Thailand were used to predict the area under the curve in 24 h/MIC >400 and trough concentration (Ctrough) <20 mg/L of 9 vancomycin dosage regimens for Thai patients stratified by age and renal function. Results: Vancomycin dosing at least 2.5 g per day can attain cumulative fraction of response (CFR) of =90% in every age group. Vancomycin dosage achieving CFR of =90% for simulated patients with creatinine clearance (CLcr) was calculated using the Cockcroft-Gault equation. Appropriate vancomycin doses for Thai patients infected with MRSA with CLcrof <40, 40-60, >60-80, and >80 mL/min were 1.5 g every 24 h, 1.25 g every 12 h, 1 g every 8 h, and 1.75 g every 12 h, respectively. However, more than a half of patients simulated using these regimens have a vancomycin Ctroughof >20 mg/L. Conclusions: Although vancomycin doses attaining a CFR of =90% can treat MRSA infection effectively, the regimens may cause kidney injury. The regimens have a probability of target attainment of 100%, and most patients can attain Ctroughof <20 mg/L.